1996
DOI: 10.1016/s0008-6363(96)00148-4
|View full text |Cite
|
Sign up to set email alerts
|

Plasma endothelin in congestive heart failure: effect of the ACE inhibitor, fosinopril

Abstract: Treatment of patients with congestive heart failure with the angiotensin-converting enzyme inhibitor, fosinopril, reduce the elevated plasma endothelin level to normal values. The relation between plasma endothelin and clinical parameters indicates that endothelin may play a pathophysiological role in the progression of congestive heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(14 citation statements)
references
References 0 publications
0
12
0
2
Order By: Relevance
“…The neurohumoral axis is typically activated in the heart failure patient, and in this regard endothelin, a potent vasoconstrictor, may play an important pathogenic role in the progression of CHF. In this regard, plasma endothelin concentrations were found to be elevated at baseline in a group of 34 patients with moderately severe CHF (39). When this cohort of patients was given 12 weeks of fosinopril treatment, not only did exercise tolerance improve significantly but endothelin concentrations normalized.…”
Section: Congestive Heart Failurementioning
confidence: 86%
“…The neurohumoral axis is typically activated in the heart failure patient, and in this regard endothelin, a potent vasoconstrictor, may play an important pathogenic role in the progression of CHF. In this regard, plasma endothelin concentrations were found to be elevated at baseline in a group of 34 patients with moderately severe CHF (39). When this cohort of patients was given 12 weeks of fosinopril treatment, not only did exercise tolerance improve significantly but endothelin concentrations normalized.…”
Section: Congestive Heart Failurementioning
confidence: 86%
“…Через 4 нед. лече-ния ЭЗВД увеличилась до 7,5 ± 2,9% (р<0,05 [7,8]. Для фозиноприла характерно меньшее количество побочных эффектов по сравнению с другими представителями этого класса лекарственных препаратов, в частности более редкое возникновение кашля, что позволяет рассчитывать на хорошую компла-ентность пациентов к лечению.…”
Section: результаты и обсуждениеunclassified
“…Accordingly, a study by Minamino et al (1997) found that ECE-1 may contribute to the process of injury-induced neointimal formation and atherosclerosis through increased production of ET-1, which could be blocked using the ECE-1 inhibitor phosphoramidon. Likewise, blocking the elevated ECE-1 expression levels in failing human hearts helps reduce elevated plasma ET-1 levels to normal values, which results in additional arterial vasodilatation, improved cardiac index, and decreased systemic and pulmonary vascular resistance (Galatius-Jensen et al, 1996).…”
Section: Targeting the Elevated Levels Of Et-1 In Pathologic Conditionsmentioning
confidence: 99%